Pengaruh Komitmen Organisasi dan Kepuasan Kerja terhadap Kinerja Karyawan BPJS Kesehatan Cabang Langsa - Abdul Latief; Syardiansah Syardiansah; Muhammad Safwan (IAIN Langsa, 2019)
The study aimed to determine the eff ect of organizational commitment and job satisfaction on the performance of Langsa Health BPJS employees. The population in this study were permanent employees at the Langsa Health BPJS, which numbered 31 respondents. The sampling technique used in this study is non probability sampling using saturated sampling. The method of data analysis uses multiple linear regression equations with the help of SPSS software carried out t test, F test and the coeffi cient of determination. The results of multiple linear regression obtained by the equation Y = 1,098 + 0,260X1 + 0,290X2. To prove the hypothesis partially carried out t test for each variable, where the organizational commitment variable obtained t sig <5% (0.03 <0.05) so that it can be stated that organizational commitment has a signifi cant eff ect on the performance of BPJS health employees in Langsa City. Job satisfaction variables obtained t sig <5% (0.04 <0.05) so that it can be stated that job satisfaction has a signifi cant eff ect on the performance of BPJS health employees in Langsa City. And to prove the hypothesis simultaneously the F test is carried out, so that F sig <5% (0.00 <0.05) can be stated that organizational commitment and job satisfaction simultaneously have a significant eff ect on the performance of BPJS employees in Langsa City. As well as the determination coefficient test results obtained by 33.4% organizational commitment and job satisfaction affect the performance of health workers BPJS Langsa City.